Geographical Constraints to Growth in Bolivia - Lykke E. Andersen; Osvaldo Nina (Institute for Advanced Development Studies (INESAD), 2007)
This paper seeks to test to which extent geographical constraints can be blamed for Bolivia s poor growth performance during the last three decades. Although geographical characteristics are too stable to explain the dramatic fluctuations in growth rates over time in Bolivia, there are at least four factors that contribute to changing the importance of those characteristics over time: 1) internal migration, 2) infrastructure investments, 3) change in export partners, and 4) change in export products. The results show that Bolivia is indeed adjusting in all 4 dimensions in order to reduce the importance of geographical constraints, but not nearly fast enough.
Keywords: Q56; R11; 330; Geography; Development; Bolivia